Nutritional, antioxidant and microbiological properties of finger millet-based beverages as influenced by starch source during lactic acid fermentation - Duodu, Kwaku Gyebi (University of Pretoria, 2022)
Dissertation (MSc (Food Science))--University of Pretoria, 2021.